Curvature and Stress Effects on the Performance of Contour‐Mode Resonant ΔE Effect Magnetometers. Issue 9 (27th June 2021) - Matyushov, Alexei D.; Spetzler, Benjamin; Zaeimbashi, Mohsen; Zhou, James; Qian, Zhenyun; Golubeva, Elizaveta V.; Tu, Cheng; Guo, Yingxue; Chen, Brian F.; Wang, Damo; Will‐Cole, Alexandria; Chen, Huaihao; et al.
Abstract: Miniaturized piezoelectric/magnetostrictive contour‐mode resonators are effective magnetometers by exploiting the Δ E effect. With dimensions of ≈100–200 µm across and <1 µm thick, they offer high spatial resolution, portability, low power consumption, and low cost. However, a thorough understanding of the magnetic material behavior in these devices is lacking, hindering performance optimization. This manuscript reports on the strong, nonlinear correlation observed between the frequency response of these sensors and the stress‐induced curvature of the resonator plate. The resonance frequency shift caused by DC magnetic fields drops off rapidly with increasing curvature: about two orders of magnitude separate the highest and lowest frequency shift in otherwise identical devices. Similarly, an inverse correlation with the quality factor is found, suggesting a magnetic loss mechanism. The mechanical and magnetic properties are theoretically analyzed using magnetoelastic finite‐element and magnetic domain‐phase models. The resulting model fits the measurements well and is generally consistent with additional results from magneto‐optical domain imaging. Thus, the origin of the observed behavior is identified and broader implications for the design of nanomagnetoelastic devices are derived. By fabricating a magnetoelectric nanoplate resonator with low curvature, a record‐high DC magnetic field sensitivity of 5 Hz nT –1 is achieved. Abstract : An ensemble of microscopic, resonant magnetometers operating on the Δ E effect is microfabricated, and the mechanical and magnetic properties are analyzed by optical methods. A strong, nonlinear correlation between sensor frequency response and curvature of the resonator plates is identified. Magnetoelastic modeling is performed to explain the magnetic behavior and to elicit implications for fabricating other types of magnetoelastic devices.